Explicit Multi-Symplectic Method for a High Order Wave Equation of KdV Type (Communications in Mathematical Research, 2019)
In this paper, we consider multi-symplectic Fourier pseudospectral methodfor a high order integrable equation of KdV type, which describes many importantphysical phenomena. The multi-symplectic structure is constructed for the equation,and the conservation laws of the continuous equation are presented. The multi-symplecticdiscretization of each formulation is exemplified by the multi-symplecticFourier pseudospectral scheme. The numerical experiments are given, and the resultsverify the efficiency of the Fourier pseudospectral method.
Keywords: the high order wave equation of KdV type; multi-symplectic theory; Hamilton space; Fourier pseudospectral method; local conservation law